2016
DOI: 10.3747/co.23.2806
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Leukemia Stem Cells: Which Pathways Drive Self-Renewal Activity in T-Cell Acute Lymphoblastic Leukemia?

Abstract: T-Cell acute lymphoblastic leukemia (t-all) is a malignancy of white blood cells, characterized by an uncontrolled accumulation of T-cell progenitors. During leukemic progression, immature T cells grow abnormally and crowd into the bone marrow, preventing it from making normal blood cells and spilling out into the bloodstream. Recent studies suggest that only discrete cell populations that possess the ability to recreate the entire tumour might be responsible for the initiation and propagation of t-all. Those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 79 publications
(107 reference statements)
0
20
0
Order By: Relevance
“…We could identify 94 gene products and 47 molecular pathways that had close to 1 AUC scores for the ALL-normal comparison (Supplementary dataset S4, Table 1). Among those, branches of Akt signaling [24], cAMP [25], cytoplasmic and mitochondrial apoptosis [26], PTEN [27], ATM checkpoint [28], Hedgehog [29], HGF [30], GSK3 [31], Estrogen and Glucocorticoid reception [32, 33], IGF1R [34], IL2 [35], TNF [36], ILK [37], JAK-STAT [38], JNK [39], mTOR [40], TGF-beta [41], Ras [42], PPAR [43], NGF [44], VEGF [45], Wnt [46], HIF1 and Notch signaling [47] were previously reported in the literature as ALL-associated pathways. However, the identified GPCR and TRAF-associated apoptosis marker pathways were new, thus representing ~4% of the total ALL-specific pathways.…”
Section: Resultsmentioning
confidence: 99%
“…We could identify 94 gene products and 47 molecular pathways that had close to 1 AUC scores for the ALL-normal comparison (Supplementary dataset S4, Table 1). Among those, branches of Akt signaling [24], cAMP [25], cytoplasmic and mitochondrial apoptosis [26], PTEN [27], ATM checkpoint [28], Hedgehog [29], HGF [30], GSK3 [31], Estrogen and Glucocorticoid reception [32, 33], IGF1R [34], IL2 [35], TNF [36], ILK [37], JAK-STAT [38], JNK [39], mTOR [40], TGF-beta [41], Ras [42], PPAR [43], NGF [44], VEGF [45], Wnt [46], HIF1 and Notch signaling [47] were previously reported in the literature as ALL-associated pathways. However, the identified GPCR and TRAF-associated apoptosis marker pathways were new, thus representing ~4% of the total ALL-specific pathways.…”
Section: Resultsmentioning
confidence: 99%
“…57 This data derives from solid tumor investigation; evidence is still needed in relation to leukemia, but those trials definitely demonstrated the complex and ambiguous role of HIFs in cancer.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%
“…RNA purity was verified by OD 260 /OD 280 nm absorption ratio. Complementary DNA (cDNA) was synthesized using SuperScript ™ First Strand Synthesis System for reverse transcriptase-polymerase chain reaction (RT-PCR; Invitrogen, USA), 2 µg of total RNA, and Oligo(dT) [12][13][14][15][16][17][18] Primers according to the manufacturer's instructions.…”
Section: Total Rna Extraction and Complementary Dna Synthesismentioning
confidence: 99%
“…9 Deregulated activation of the canonical Wnt pathway is also observed in leukemia. 1,[10][11][12][13] The hematopoietic system of the adult organism is composed of cells with a short life span, which are renewed by differentiating from a small population of hematopoietic stem cells (HSCs). Nuclear β-catenin is a key molecule that drives self-renewal.…”
Section: Introductionmentioning
confidence: 99%